Penerapan model pembelajaran problem based learning terhadap hasil belajar IPA siswa kelas V SD - Puspita, Jaya Angga Dwi (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Teacher-centered learning and lack of student involvement in learning activities can trigger low student learning outcomes. This study aims to describe the learning outcomes of fifth grade elementary school students in science subjects. The research method used by the researcher is a quantitative descriptive approach, the research subjects are students of class VA with a total of 30 students, data collection techniques use tests. The test used is to determine the learning outcomes of class V students on food chain material in an ecosystem, the results show that science learning outcomes are categorized very high as many as 14 of 30 students or 46.66 percent, learning outcomes with categories high as many as 13 of 30 students or 43.33 percent, and learning outcomes in the medium category as many as 3 students or 10 percent. The average student learning outcomes in class VA on food chain material in an ecosystem is 80.00 with a high category. Therefore, the conclusion obtained is that the science learning outcomes of fifth grade students can be categorized as high.